Chatbot and ChatGPT Publication Trends: A Bibliometric Analysis - Gujjarappa, Nagaraja L; Babu H, Rajendra; Chandrashekara, M (Journal of Data Science, Informetrics, and Citation Studies, 2026)
Artificial Intelligence tools like ChatGPT and chatbots are designed to replicate intelligent human-to-human conversation. At the end of 2022, ChatGPT was a trending topic and discussed across the sectors, it was discussed in the media. Journalists and experts exchanged numerous thoughts and suggestions. ChatGPT also created worries among academics as students may utilize ChatGPT to write essays and projects. This study’s primary goal is to identify trends in publication and to realize the visualisation network of co-authorship of countries, co-occurrence of keywords, co-citation and citation of authors, countries and bibliographic linkage or coupling examination in ChatGPT and Chatbot research. The study employed a bibliometric approach. Data was extracted using the Clarivate Web of Science (WoS) database. The terms “OpenAI”, “ChatGPT”, “Chatbot, “Generative Model”, and “Generative Pre-Trained Transformer (GPT)” were used to search the publications and we found 6391 documents that were published between 1990 and 2023. The bibliometric networks of publications are visualized using the VOSviewer. Results revealed that the highest (2288) number of research published in 2023 and publications increased rapidly yearly. Most of the publications are contributed by the USA, China, the UK, Germany and Canada. Elsevier, Springer Nature, IEEE, MDPI and Wiley are the top publishers that contributed more research. This analysis provides a thorough understanding of ChatGPT and Chatbot. It will be helpful for both those studying and applying AI in their professional and academic endeavours.
Keywords: Artificial Intelligence; Bibliometrics; Chatbot; ChatGPT; Education; Network Analysis; OpenAI